Biomarkers Predict Relapse in Granulomatosis with Polyangiitis. (30th April 2014) - Hogan, Patrick C. P.; O'Connell, Robert M.; Scollard, Simone; Browne, Emmett; Hackett, Emer E.; Feighery, Conleth
Abstract : Granulomatosis with polyangiitis (GPA) is a small blood vessel vasculitic disorder with a high mortality rate if undiagnosed or treated inadequately. Disease relapse is a key feature of this disease and early identification of relapse episodes is very important in limiting end-organ damage. The advent of indirect immunofluorescence to detect antineutrophil cytoplasmic antibody (ANCA) with specific reactivity against the enzyme proteinase-3 (PR3) has been very useful in the diagnosis of GPA but is less helpful in predicting relapse. Indeed, up to date no satisfactory biomarker has been identified that can reliably predict relapse. This study assessed the probability of the occurrence of a relapse when a change was noted in a range of commonly used laboratory tests. These tests included levels of C-reactive protein (CRP), anti-PR3 antibodies, ANCA titre, and the neutrophil count. A group of 30 GPA patients with a total of 66 relapse episodes was investigated and a novel clinical yield score was devised. When a combined rise in CRP, anti-PR3 antibodies, and neutrophil count was observed in the 6-month period before a relapse event, 59% of patient relapses could be predicted. Monitoring changes in this set of parameters helps identify disease relapse.